In Vitro Low Responsiveness of Leishmania donovani Towards Sodium Antimony Gluconate - Alam, Murshed; Shamsuzzaman, AKM; Musa, AKM; Khan, Abul Hossain; Mahmud, Md Chand; Ahmed, Mesbah Uddin; Hossain, Md. Akram; Ahmed, Abdullah Akhtar (Bangladesh Journal of Medical Microbiology, 2016)
Kala-azar has been uprising concomitantly with drug-resistant strains of the causatinve agent, particularly in the neighbouring India. The actual perspective of drug resistance in Leishmania donovani in Bangladesh is yet to be explored. So, this prospective study, as a preliminary one, was done to observe in vitro drug responsiveness against Sodium Antimony Gluconate (SAG) and Amphotericin B of 41 strains of L. donovani isolated from Kala-azar cases. The cases (n=41) were selected from 45 clinically suspected febrile patients those who were positive for Kala-azar by immunochromatographic test (ICT). The selected cases were subsequently confirmed as Kala-azar by detection of Leishmania Donovan (LD) bodies from bone marrow aspirates (n=38) by microscopy and/or showing promastigotes in modified McNeal, Nicole and Novy (NNN) media (n=41). Minimum Inhibitory Concentrations (MICs) of SAG and Amphotericin B were seen in relation with history of previous SAG therapy of the patients. Among 08 strains with previous SAG therapy, MICs of SAG were 500 µg in 05 (62.5%) and 250 µg in 03 (37.5%) cases. In remaining 33 strains with no previous SAG therapy, MIC of the drug was 250 µg. In all 41 strains, MIC of Amphotericin B was 05 µg irrespective of the history of previous SAG therapy. The study revealed that strains of L. donovani with low responsiveness to standard dose of pentavalent antimonials have been started to appear in our community that needs further study at community level in a larger population. Bangladesh J Med Microbiol 2008; 02 (01): 8-12 DOI: http://dx.doi.org/10.3329/bjmm.v2i1.21782